Analysis of The Implementation of Occupational Safety and Health (K3) on Employee Performance Efficiency At UD Industri Tahu Tiga "S" Prima In Batu City - Memelia Elvira; Gunawan, Cakti Indra; Yuni Setyowati (International Journal of Management and Business, 2025)
This research aims to evaluate the implementation of Occupational Safety and Health (K3) and its impact on employee performance efficiency at UD Industri Tahu Tiga "S" Prima in Batu City. The study underscores the significance of an effective K3 system in minimizing accident risks while enhancing employee performance. It adopts a qualitative research approach with a descriptive, in-depth analysis. The sampling method used is purposive sampling, targeting specific informants. Data collection methods include field research with primary data through interviews, documentation, and observations, as well as library research for secondary data. The study also references literature and journal articles related to the case. The findings reveal that the implementation of K3 at UD Industri Tahu Tiga "S" Prima in Batu City remains suboptimal, with many employees neglecting Personal Protective Equipment (PPE) and overlooking work accident risks. In the tofu production process, stages like soybean grinding, boiling, filtering, molding, cutting, and frying present potential accident hazards, which the company needs to address to ensure employee safety and well-being, providing a sense of comfort and security at work.